Screening and clinical characteristics analysis of familial hypercholesterolemia in a tertiary public hospital - Shen, Tianzhou; Fu, Qingan; Luo, Renfei; Wan, Yixin; Jiang, Long (Frontiers in Cardiovascular Medicine, 2023)
Background and aims: Familial hypercholesterolemia (FH) is becoming a global burden.However, it remains underdiagnosed and undertreated worldwide. This study aimed to observe the screening rate of FH patients and department distribution among hospitalized patients using different diagnostic criteria.: A total of 45,410 inpatients with LDL-C ≥ 3.5 mmol/L between 2008 and 2019 were included from The Second Affiliated Hospital of Nanchang University. Inpatients are diagnosed and divided into groups by Dutch Lipid Clinic Network (DLCN) criteria, Chinesemodified DLCN criteria and Chinese expert consensus (CEC) criteria.Results: There were 172, 1076 and 115 inpatients included in the DLCN group, Chinesemodified DLCN group and CEC group, respectively (screening rates: 0.38%, 2.37% and 0.25%).These FH patients had a very high risk of atherosclerotic cardiovascular disease (ASCVD) (55.7%-74.4%), especially in the DLCN group and CEC group (70.4%-74.4%). More than half of the patients were in the Department of Cardiology, and other high-risk departments included Neurology, Nephrology, Vascular Surgery, Otolaryngology & Head Neck Surgery and Traditional Chinese Medicine (24.35%-31.51%). Overall, hypertension, coronary heart disease, carotid arteriosclerosis, hepatic cyst, arrhythmia, and nonalcoholic fatty liver disease were common accompanying diseases with FH.It is necessary to establish appropriate diagnostic criteria and more positive treatment strategies for the FH inpatient population. In addition, promoting awareness of FH among doctors from other departments is also necessary. Therefore, developing a comprehensive management strategy for FH disease is very important.